8
$\begingroup$

The Fibonacci polynomials are defined recursively by $F_0(x)=0, F_1(x)=1$ and $F_n(x)=xF_{n-1}(x)+F_{n-2}(x)$, for $n\geq2$.

While computing certain integrals, I observe the following (numerically) which prompted me to ask:

Question. For $n, k\in\mathbb{N}$, are these always integers? $$\int_0^1F_n(k+nz)\,dz$$

To help clarify, here is a list of the first few polynomials: $$F_2(x)=x, \qquad F_3(x)=x^2+1, \qquad F_4(x)=x^3+2x.$$

$\endgroup$
4
  • 1
    $\begingroup$ Did you check the case n=3 and k=1? $\endgroup$ Jun 26 '17 at 0:05
  • 1
    $\begingroup$ Perhaps you were misled by a typo: $F_0(x)=0$. $\endgroup$ Jun 26 '17 at 0:08
  • $\begingroup$ $F_3(1+3z)=9z^2+6z+2$, so $\int_0^1F_3(1+3z)dz=8$. $\endgroup$ Jun 26 '17 at 2:10
  • $\begingroup$ The first few $F_n=\sum F(n,k)x^k$ at least have the stronger property that every term of $\sum \int \ldots$ is an integer separately. If this is true in general, one can perhaps be optimistic about a proof since there is an explicit formula for the coefficients $F(n,k)$. $\endgroup$ Jun 26 '17 at 2:52
14
$\begingroup$

The integral of each individual monomial will be integral. First we have the identity $$F_n(x)=\sum_{i=0}^{\lfloor(n-1)/2\rfloor}{n-i-1\choose i}x^{n-2i-1},$$ so my claim is that $$\binom{n-i-1}{i}\int_0^1 (k+nz)^{n-2i-1}dz=\binom{n-i-1}{i}\cdot\frac{(k+n)^{n-2i}-k^{n-2i}}{n(n-2i)} \in \mathbb Z.$$ By the binomial theorem we can write $(k+n)^{n-2i}=k^{n-2i}+nk^{n-2i-1}(n-2i)+n^2d$ for some integer $d$. So we can write $$\binom{n-i-1}{i}\cdot\frac{(k+n)^{n-2i}-k^{n-2i}}{n(n-2i)}=k^{n-2i-1}\binom{n-i-1}{i}+d\cdot\frac{n}{n-2i}\binom{n-i-1}{i}$$ it suffices to show that $\frac{n}{n-2i}\binom{n-i-1}{i}$ is an integer. However we can check that $$\frac{n}{n-2i}\binom{n-i-1}{i}=\binom{n-i-1}{i}+2\binom{n-i-1}{i-1}$$ and the claim follows.

$\endgroup$
1
  • 2
    $\begingroup$ Great job, as always! $\endgroup$ Jun 26 '17 at 17:58
0
$\begingroup$

A different view is given with direct use of the Lucas polynomials. Using the relation $$\frac{d}{dx} \, L_{n}(x) = n \, F_{n}(x)$$ then the integral becomes \begin{align} \int_{0}^{1} F_{n}(k + n \, t) \, dt &= \frac{1}{n} \, \int_{k}^{k+n} F_{n}(u) \, du \\ &= \frac{1}{n^2} \, \int_{k}^{k+n} \frac{d}{du} \, L_{n}(u) \, du \\ &= \frac{L_{n}(n+k) - L_{n}(k)}{n^2}. \end{align} Since $L_{-n}(x)$ and $L_{n}(-x)$ have relations to $L_{n}(x)$ then the restrictions on $n$ and $k$ become $n \neq 0$. Since the Lucas polynomials evaluated at $x=\text{ integers}$ are integers then the integral evaluates to integers dependent upon $n$ and $k$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.